2016
DOI: 10.1016/j.tra.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Waiting time perceptions at transit stops and stations: Effects of basic amenities, gender, and security

Abstract: a b s t r a c tWaiting time in transit travel is often perceived negatively and high-amenity stops and stations are becoming increasingly popular as strategies for mitigating transit riders' aversion to waiting. However, beyond recent evidence that realtime transit arrival information reduces perceived waiting time, there is limited empirical evidence as to which other specific station and stop amenities can effectively influence user perceptions of waiting time. To address this knowledge gap, the authors cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(111 citation statements)
references
References 46 publications
(65 reference statements)
5
105
1
Order By: Relevance
“…Comfort while waiting at station/stop is a performance factor for conventional bus and BRT, but it is an excitement factor for metro transit. Waiting time is more important than in-vehicle travel time (TCRP, 2003) and amenities at station/stop influence riders' perception of waiting time (Fan, Guthrie, & Levinson, 2016). Therefore, comfort while waiting is important for transit riders.…”
Section: 2mentioning
confidence: 99%
“…Comfort while waiting at station/stop is a performance factor for conventional bus and BRT, but it is an excitement factor for metro transit. Waiting time is more important than in-vehicle travel time (TCRP, 2003) and amenities at station/stop influence riders' perception of waiting time (Fan, Guthrie, & Levinson, 2016). Therefore, comfort while waiting is important for transit riders.…”
Section: 2mentioning
confidence: 99%
“…While a great deal of design effort has focussed on the interior comfort of transit vehicles, it is also found that conditions of access to the rail or bus stop as well as the facilities at the stop played an important role in the degree of satisfaction with the service [21]. Estimated waiting time at bus stops varied considerably as a function of the provision of benches and enclosures [22]. At rail stations in Grenoble, heating and ventilation, along with other factors in comfortable waiting conditions had significant impact on perceived waiting time [23].…”
Section: Travel Experience and Mode Choicementioning
confidence: 99%
“…A growing interest in analyzing traffic problems in developing countries has been witnessed over the years [5]- [8]. Systems like [9], [10] are among the recent studies that attempted to estimate passengers' waiting time distributions and perceptions, depending on service and stations characteristics. There are many definitions of the waiting time.…”
Section: Introductionmentioning
confidence: 99%
“…The first expresses it as the ratio of the actual *Electrical Engineering department, Aswan faculty of Engineering, Aswan University, Egypt, 81542. time waiting (either for getting on a vehicle or In-Vehicle Time (IVT)) to the scheduled time [11]. The second, adopted by transportation models, assumes that average waiting times are half the service headway given random passenger arrivals [9], [10]. The definition adopted in this paper is the first one.…”
Section: Introductionmentioning
confidence: 99%